2017
DOI: 10.1165/rcmb.2016-0418oc
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Pulmonary Endothelial Hemoglobin α Improves Nitric Oxide Signaling and Reverses Pulmonary Artery Endothelial Dysfunction

Abstract: Pulmonary hypertension is characterized by pulmonary endothelial dysfunction. Previous work showed that systemic artery endothelial cells (ECs) express hemoglobin (Hb) α to control nitric oxide (NO) diffusion, but the role of this system in pulmonary circulation has not been evaluated. We hypothesized that up-regulation of Hb α in pulmonary ECs contributes to NO depletion and pulmonary vascular dysfunction in pulmonary hypertension. Primary distal pulmonary arterial vascular smooth muscle cells, lung tissue se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…Indeed, anemia has been commonly reported as a side effect during the clinical trials of hsp90 inhibitor drug candidates (35,36). Regarding Hb expression in nonerythroid cells, the Hb-α expressed in pulmonary endothelial cells was recently shown to regulate NO control of pulmonary blood pressure and to present an effective target for therapeutic intervention (37). Hb-β expression in lung tissues was found to be antimetastatic (38), while its expression in a variety of tumor cells increased their metastatic potential, possibly by enhancing tumor-cell survival during blood-born dissemination (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, anemia has been commonly reported as a side effect during the clinical trials of hsp90 inhibitor drug candidates (35,36). Regarding Hb expression in nonerythroid cells, the Hb-α expressed in pulmonary endothelial cells was recently shown to regulate NO control of pulmonary blood pressure and to present an effective target for therapeutic intervention (37). Hb-β expression in lung tissues was found to be antimetastatic (38), while its expression in a variety of tumor cells increased their metastatic potential, possibly by enhancing tumor-cell survival during blood-born dissemination (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work identified that cytochrome b5 reductase 3 (Cyb5R3), also known as methemoglobin reductase, serves as the primary reductase controlling heme iron redox cycling (Fe 3+ → Fe 2+ ) of α-globin, as well as other nonerythroid globins (3). The Genetic knockdown of α-globin or disruption of the α-globin-eNOS complex using a peptide mimetic increases NO signaling, promoting vasodilation and lowering blood pressure (3,13,14). A challenge to this signaling paradigm is that α-globin alone is unstable and cytotoxic, particularly in its oxidized state (Fe 3+ ), which forms via dioxygenation (15).…”
Section: α-Globin Heme Redox Cycling: Can Enos Do It All?mentioning
confidence: 99%
“…While many complex mechanisms may compensate for the blood pressure control in these individuals in the steady state, it is possible that stress-specific conditions may increase endothelial cell α-globin expression and modify NO signaling. A recent study showed that in the setting of pulmonary hypertension, α-globin expression increases and may contribute to the low NO signaling state routinely observed in pulmonary arteries (14). In addition, conditions that increase the expression of Kruppel-like factors (KLFs) such as KLF-2 or KLF-4, which are also known to increase α-globin expression, may also participate in human vascular disease and NO control (21).…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
“…By contrast, when Hbα is in the reduced Fe 2+ state, NO is intercepted and signaling between endothelium and smooth muscle cells types is blunted, decreasing NO-sGC-cGMP-mediated vasodilation. 97,98,99 Studies have demonstrated that disruption of Hbα coupling to eNOS with a Hbα-mimetic peptide enhanced NO-sGC-cGMP-dependent dilation of resistance arteries in both the systemic and pulmonary circuits. 100,101 In endothelial cells, pharmacological inhibition of flavoprotein NADH cytochrome B5 reductase 3 (Cyb5R3), otherwise known as methemoglobin reductase, facilitates NO signaling via the MEJ.…”
Section: Reactive Nitrogen Speciesmentioning
confidence: 99%
“…97,98,99 Studies have demonstrated that disruption of Hbα coupling to eNOS with a Hbα-mimetic peptide enhanced NO-sGC-cGMP-dependent dilation of resistance arteries in both the systemic and pulmonary circuits. 100,101 In endothelial cells, pharmacological inhibition of flavoprotein NADH cytochrome B5 reductase 3 (Cyb5R3), otherwise known as methemoglobin reductase, facilitates NO signaling via the MEJ. 102,103 In VSMC’s, a recent study showed a new role of Cyb5R3 where it functions to reduce sGC from its Fe 3+ to its Fe 2+ state.…”
Section: Reactive Nitrogen Speciesmentioning
confidence: 99%